Improving Science Learning Outcomes Material Properties of Light (Principle Lup Work) with Experimental Methods in Class IV A Students SDN Tempel Semester 1 Academic Year 2021/2022 - Dwi Mulyani (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This research was made with the aim of improving learning outcomes on the properties of light (the working principle of the loop), changing behavior and learning motivation on the material properties of light (the working principle of the loop) in class IV A students at SDN Tempel Surakarta Semester 1 Academic Year 2021/ 2022 with the application of the experimental method. This research is a Classroom Action Research conducted on 14 students in class IV A in 2 cycles. The action stages in improving learning are planning, implementing, observing, and reflecting. The results showed that there was an increase in learning outcomes in the cognitive aspects of the initial conditions / pre-cycle there were 28.6% of students who achieved learning mastery, an increase of 50% in cycle I and an increase of 100% in cycle II. The increase in learning outcomes also occurred in the psychomotor aspect. In cycle I, there were 6 students (42.9%) who were very capable, capable and sufficiently capable of conducting experiments on the material properties of light (the working principle of the loop). In cycle II the number of students who are very capable, capable, and quite capable of conducting material experiments on the properties of light (the working principle of the loop) increases to 13 students (92.9%), the increase in student learning activity is 35.7% in cycle I to 85.7% of students in cycle II.